Virtualios laimės beieškant: naudojimasis socialiniais tinklais siekiant pozityvių emocijų iš dalies kompensuoja neigiamą vienišumo ir nerimastingumo efektą gerovei - Kymantienė, Justina; Žiedelis, Arūnas; Bulotaitė, Laima (Psichologija, 2023)
For some time now, social networks have become a common medium for everyday social interactions. Every year, users spend more and more time on social networks, and the motives and results of such activities for well-being are mixed. It is observed that the use of social networks motivated by the expectancies to avoid negative emotions is more associated with negative consequences, but it remains unclear what role the expectancies of experiencing positive emotions play in the well-being of the social network user. This study aimed to verify the significance of using social networks to experience positive emotions in compensating for the negative effect of two important risk factors – loneliness and trait anxiety on well-being. 201 social network users aged between 18 and 69 participated in the study. Respondents were given instruments that assessed their loneliness, trait anxiety, use of social networks to experience positive emotions, and well-being. The results confirmed the negative associations between loneliness, trait anxiety and well-being. Moderation analysis also revealed that the use of social networks to experience positive emotions offset the negative effect of loneliness and trait anxiety on well-being. Those lonely and anxious subjects who used social networks more often for positive emotions were characterized by higher well-being.
Keywords: naudojimosi socialiniais tinklais lūkesčiai; vienišumas; nerimastingumas; gerovė